Self-limiting Ibrutinib-Induced Neutrophilic Panniculitis. (February 2018) - Stewart, Jacob; Bayers, Stephanie; Vandergriff, Travis
Abstract : Abstract: Neutrophilic panniculitis is a relatively rare condition, characterized by predominantly neutrophilic inflammation in the subcutaneous fat. Rarely, neutrophilic panniculitis may be induced by chemotherapeutics or targeted molecular therapies, including the Bruton tyrosine kinase inhibitor ibrutinib. Previously reported cases of ibrutinib-induced panniculitis were suppressed with sustained low-dose steroid therapy while continuing ibrutinib therapy. To our knowledge, self-limiting panniculitis during ibrutinib therapy has not yet been described. We describe a case of self-limiting, neutrophilic panniculitis which developed during ibrutinib therapy. A 78-year-old woman presented to the dermatology clinic with a 3-week history of painful erythematous nodules on her lower extremities which occurred 1 month after initiating ibrutinib therapy for chronic lymphocytic leukemia. Physical examination revealed tender erythematous poorly demarcated subcutaneous nodules on the anterior and posterior aspects of both lower legs. A panniculitis was suspected clinically, and a punch biopsy was performed. Histological evaluation revealed a lobular panniculitis with fat necrosis and infiltrates consisting predominantly of neutrophils. A diagnosis of neutrophilic panniculitis was rendered, which the patient opted not to treat. The eruption waned before resolving spontaneously over the course of 6 months despite continued ibrutinib therapy. This case illustrates panniculitis as an emerging adverse drug reaction after treatment with ibrutinib and that not all cases will require ibrutinib dose adjustment or steroid therapy but rather may be subject to spontaneous resolution.